Maternal nutrient restriction during late gestation and early postnatal growth in sheep differentially reset the control of energy metabolism in the gastric mucosa - Sebert, S.P.; Dellschaft, N.S.; Chan, L.L.Y.; Street, H.; Henry, M.; Francois, C.; Sharma, V.; Fainberg, Hernan P.; Patel, N.; Roda, J.; Keisler, D.; Budge, H.; et al. (Endocrine Society, 2011)
Fetal growth restriction followed by accelerated postnatal growth contributes to impaired metabolic function in adulthood. The extent to which these outcomes may be mediated centrally within the hypothalamus, as opposed to in the periphery within the digestive tract, remains unknown. In a sheep model, we achieved intrauterine growth restriction experimentally by maternal nutrient restriction (R) that involved a 40% reduction in food intake through late gestation. R offspring were then either reared singly to accelerate postnatal growth (RA) or as twins and compared with controls also reared singly. From weaning, all offspring were maintained indoors until adulthood. A reduced litter size accelerated postnatal growth for only the first month of lactation. Independently from postnatal weight gain and later fat mass, R animals developed insulin resistance as adults. However, restricted accelerated offspring compared with both the control accelerated and restricted restricted offspring ate less and had higher fasting plasma leptin as adults, an adaptation which was accompanied by changes in energy sensing and cell proliferation within the abomasum. Additionally, although fetal restriction down-regulated gene expression of mammalian target of rapamycin and carnitine palmitoyltransferase 1-dependent pathways in the abomasum, RA offspring compensated for this by exhibiting greater activity of AMP-activated kinase-dependent pathways. This study demonstrates a role for perinatal nutrition in the peripheral control of food intake and in energy sensing in the gastric mucosal and emphasizes the importance of diet in early life in regulating energy metabolism during adulthood.